2014
DOI: 10.1016/j.envres.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Asthma, respiratory symptoms and lung function in children living near a petrochemical site

Abstract: Residential proximity to environmental hazards has been related to adverse health outcomes. Respiratory health and allergies in children living near petrochemical sites have not been extensively studied. We evaluated the association between residential proximity to the petrochemical site of Tarragona (Catalonia, Spain) and the prevalence of asthma, respiratory symptoms and lung function in children. Children aged 6-7 (n=2672) and adolescents aged 13-14 (n=2524) residing near two large petrochemical sites and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 42 publications
1
35
0
2
Order By: Relevance
“…Various studies have examined the association of petrochemical industries in the residential areas and the health effects in the respective population, including children. (Rovira et al, 2014;Mukesh et al, 2004;White et al, 2009;Smargiassi et al, 2009;Wichmann et al, 2009;Brunekreef B.et al, 1995;Gauderman et al, 2005). Rovira et al (2014) studied the effect of oil refinery emissions on the asthma symptoms and lung function in children residing near the petrochemical areas.…”
Section: Petrochemical Industry and Pollutant Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have examined the association of petrochemical industries in the residential areas and the health effects in the respective population, including children. (Rovira et al, 2014;Mukesh et al, 2004;White et al, 2009;Smargiassi et al, 2009;Wichmann et al, 2009;Brunekreef B.et al, 1995;Gauderman et al, 2005). Rovira et al (2014) studied the effect of oil refinery emissions on the asthma symptoms and lung function in children residing near the petrochemical areas.…”
Section: Petrochemical Industry and Pollutant Emissionsmentioning
confidence: 99%
“…(Rovira et al, 2014;Mukesh et al, 2004;White et al, 2009;Smargiassi et al, 2009;Wichmann et al, 2009;Brunekreef B.et al, 1995;Gauderman et al, 2005). Rovira et al (2014) studied the effect of oil refinery emissions on the asthma symptoms and lung function in children residing near the petrochemical areas. The study showed that the population residing in the petrochemical areas had more episodes of respiratory symptoms (cough) and higher hospitalization rate as compared to the control population but no higher symptoms of asthma was noted.…”
Section: Petrochemical Industry and Pollutant Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The doses applied in the present study were relevant to human exposure scenarios according to a previous report (Vietti et al, 2013). The mass concentrations applied in the present study were relevant to occupational exposure scenarios in humans (Rovira et al, 2014); the alveolar surface area, breathing frequency 30 times/min, lung deposition rate 30%, minute ventilation was 20 l/min, and the recommended ZnO standard was 5 mg/m 3 (Fine et al, 1997). The human-equivalent mass concentrations were achieved at 1.36 days for 10 µg, 2.72 days for 20 µg, 6.8 days for 50 µg, and 13.6 days for 100 µg in a ZnONP-contaminated occupational environment.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The doses applied in the present study were relevant for occupational exposure scenarios in humans. 27 The mice were exposed to 100 μg/lung ZnONPs (alveolar surface area 0.05 m 2 ), which is equal to 200 mg/lung ZnONPs in humans (alveolar surface area 102 m 2 ). Considering the breathing frequency (30 times/min), lung deposition rate (30%), a minute ventilation of 20 L/min, and the recommended ZnO standard of 5 mg/m 3 , 1 a human-equivalent dose would be achieved 13.6 days in a ZnONP-contaminated occupational environment.…”
mentioning
confidence: 99%